2015
DOI: 10.1186/s13287-015-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of mouse embryonic stem cell-derived oligodendrocytes in the murine model of globoid cell leukodystrophy

Abstract: IntroductionGloboid cell leukodystrophy (GLD) is a severe disorder of the central and peripheral nervous system caused by the absence of galactocerebrosidase (GALC) activity. Cell-based therapies are highly promising strategies for GLD. In this study, G-Olig2 mouse embryonic stem cells (ESCs) were induced into oligodendrocyte progenitor cells (OPCs) and were implanted into the brains of twitcher mice, an animal model of GLD, to explore the therapeutic potential of the cells.MethodsThe G-Olig2 ESCs were induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
(44 reference statements)
0
18
1
Order By: Relevance
“…A recent cell therapy study for mice with Krabbe disease failed, because accumulation of galactosyl-ceramide and its toxic derivative psychosine killed the maturing oligodendrocytes after transplantation. 21 Our studies in patients with vanishing white matter disease showed that hyaluronan is increased in the brain extracellular matrix, 22 which impedes maturation of oligodendrocyte progenitors and may also affect transplanted oligodendrocyte progenitors.…”
Section: Stem Cell Therapymentioning
confidence: 85%
“…A recent cell therapy study for mice with Krabbe disease failed, because accumulation of galactosyl-ceramide and its toxic derivative psychosine killed the maturing oligodendrocytes after transplantation. 21 Our studies in patients with vanishing white matter disease showed that hyaluronan is increased in the brain extracellular matrix, 22 which impedes maturation of oligodendrocyte progenitors and may also affect transplanted oligodendrocyte progenitors.…”
Section: Stem Cell Therapymentioning
confidence: 85%
“…Twenty days after injection, the level of myelin was measured, as was the distribution of implanted donor cells. There was no increase in the level of myelin basic protein in treated mice, and the donor cells remained localized to the injection site (Kuai el al., ). In addition, there was no improvement in behavioral assays measuring stride length or twitching severity, and life span of treated mice was not significantly different from that of untreated mice or those injected with saline (Kuai et al, ).…”
Section: Single‐modality Therapiesmentioning
confidence: 97%
“…The transplantation process we used has been previously described. [50][51][52] Because we imitated microcosmic surgery in the brain, we transplanted cells immediately after brain injury. To avoid additional injury, we injected cells into the same hole with a depth of 2 mm, to make sure transplantation had a minimal effect on the injury we created.…”
Section: Animal Modelmentioning
confidence: 99%